The Generalization of the Extra Element Theorem for Symbolic Circuit Tolerance Analysis. (1st June 2011) - Filaretov, Vladimir; Gorshkov, Konstantin
Abstract : A new method of the symbolic circuit tolerance analysis has been proposed. The approach is based on Middlebrook's extra element theorem and the generalized parameter extraction method. It does not need the matrix network description or presentation as algebraic sets or topological graphs. The proposed techniques have been realized in the computer program (Toleralize). To verify the theoretical analysis, computer simulation results are included.